Omalizumab as an adjuvant in food allergen immunotherapy. Issue 3 (June 2021) - Dantzer, Jennifer A.; Wood, Robert A.
Abstract : Purpose of review: To review the most relevant studies in the rapidly advancing field of omalizumab as an adjunct to food allergen oral immunotherapy (OIT). Recent findings: Clinical trials have primarily focused on milk, peanut, and multiallergen OIT combined with omalizumab. These studies suggest that omalizumab in addition to OIT can decrease the time required to reach maintenance OIT dosing and adverse events; however, serious adverse events did still occur. There is limited long-term data but available information suggests that individuals are at risk for increased reactivity after stopping omalizumab, and many discontinued treatment. There has been diversity in study designs, dosing, and populations. Summary: The use of anti-IgE antibody as an adjunct to food allergen OIT has been an expanding area of research with several additional trials underway. Significant progress has been made in the past decades but further studies are needed to optimize protocols, improve safety and efficacy, and identify patients who will have the greatest benefit.